Conflict and concession: nationality in the pastorate for Althaus and Bonhoeffer. Issue 2 (19th April 2017) - Robinson, David; Tafilowski, Ryan
Abstract: In their 1920s expatriate theologies, Paul Althaus and Dietrich Bonhoeffer claim to be bound by a conflictual international 'law', which mandates violent competition while authorising the strong to displace weaker peoples. We argue that acknowledging such correspondence helps to reveal a surprising turn in their diverging ecclesiological judgements over the 1933 Aryan Paragraph. Ironically, although Althaus holds to the productivity of conflict between peoples, he supports the exclusion of Jewish pastors in Germany as a concession to fragile völkisch identity. In contrast, Bonhoeffer's new pacifist leanings coincide with his incitement to conflict on behalf of Jewish colleagues, overriding the use of Pauline admonition to defer to the 'weak' conscience.